An investigation of Australian osteopaths' attitudes, skills and utilisation of evidence-based practice: a national cross-sectional survey - Matthew J. Leach; Tobias Sundberg; Gary Fryer; Philip Austin; Oliver P. Thomson; Jon Adams (BMC, 2019)
Abstract Background Osteopaths are an integral member of the health care team, playing a pivotal role in the provision of care for patients with musculoskeletal disorders. Osteopaths, like other health care providers, are under increasing pressure to deliver evidence-based health care and to improve patient outcomes. However, the extent to which osteopaths engage in evidence-based practice (EBP), particularly in Australia, is not well understood. This study therefore set out to investigate the attitudes, skills and use of EBP, and perceived barriers and enablers of EBP uptake, among osteopaths practicing in Australia. Methods National cross-sectional survey of Australian registered osteopaths. Eligible participants were invited by email and other digital media recruitment strategies to complete the online Evidence-Based Practice Attitude and Utilisation Survey (EBASE). Results A total of 332 osteopaths completed the survey. The demographic characteristics of respondents were generally consistent with the characteristics of the Australian osteopathy workforce. The respondents were mostly favourable of EBP, with the majority agreeing or strongly agreeing that EBP assists in making decisions about patient care (86.7%) and improves the quality of patient care (75.6%). While most respondents (88.3%) had some training in EBP, most reported a moderate level of perceived skill in EBP. The majority of respondents engaged infrequently (0-5 times) in EBP activities within the last month, and most indicated that a very small or small proportion of their clinical practice was based on clinical research evidence. Leading barriers to the uptake of EBP were lack of time and lack of clinical evidence in osteopathy. Key enablers of EBP uptake were access to the internet and online databases at work, and access to full-text articles and EBP education materials. Conclusions Osteopaths participating in the survey were largely supportive of evidence-based practice, yet engaged infrequently in EBP activities. An important next step in this research is to identify suitable strategies that effectively improve EBP uptake in osteopathy, and perchance, improve patient outcomes.